Anti-reflection coatings based on SnO₂, SiO₂, Si₃N₄ films for photodiodes operating in ultraviolet and visible spectral ranges - Dobrovolskiy, Yu.G.; Perevertailo, V.L.; Shabashkevich, B.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
It is shown in this paper that tin dioxide coating is suitable to enhance sensitivity of photodiodes operating in the ultraviolet spectral range and based on zinc selenide and gallium phosphide. For these materials, the sensitivity values have been increased up to 0.12 and 0.2 A/W, respectively, in the maxima of their spectral characteristics. It is also shown that the film silicon nitride – silicon dioxide a bit better clarifies silicon photodiode, especially at the wavelength 700 nm. A gluing composition, in general, worsens transmission of films, and to greater extent transmission of the above film.